Analisis Faktor Penerimaan dan Penggunaan LinkedIn Menggunakan Model UTAUT 2 - Rahmayuni, Septa; Indah, Dwi Rosa; Firdaus, Mgs Afriyan; Wedhasmara, Ari (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
LinkedIn functions as a job search site. LinkedIn users are spread across various regions of Indonesia including Palembang City. Based on ratings on the Play Store, LinkedIn has the lowest rating compared to similar job search applications and a search on LinkedIn by entering Palembang City as a location shows the number of users in Palembang City is lower than other cities. In user reviews there are complaints about verification issues that cause displeasure and rejection of the use of this application. To find out what factors influence acceptance and use of LinkedIn, it is necessary to analyze these factors. This research was conducted by testing several constructs in the UTAUT 2 model. The data analysis technique used is the PLS-SEM analysis approach. The results showed that facilitating conditions, hedonic motivation, and habit affect behavioral intention. On the other hand, facilitating conditions and habit affect use behavior.